The Influence of Wardah’s Soft Selling Campaign on Customer Loyalty through Brand Equity among Generation Z Consumers in Tanjungpinang City - Rachel Immanuela Simanjuntak; Kiki Wulandari; Fradya Randa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Competition in the cosmetic industry in Indonesia has become increasingly intense, particularly in attracting and retaining Generation Z consumers who tend to be critical, digitally oriented, and sensitive to brand values. Wardah, as a local cosmetic brand, implements a soft selling campaign strategy that emphasizes emotional approaches, religious values, halal attributes, and storytelling rather than hard-selling promotional tactics. This study aims to analyze the effect of Wardah’s soft selling campaign on customer loyalty with brand equity as an intervening variable among Generation Z consumers in Tanjungpinang City. The research method employed a quantitative approach with an explanatory research design. Data were collected through the distribution of questionnaires to Generation Z consumers who use Wardah products in Tanjungpinang City, selected using a purposive sampling technique. The data were analyzed using path analysis to examine both direct and indirect effects among the research variables, which include soft selling campaign, brand equity, and customer loyalty. The results indicate that Wardah’s soft selling campaign has a positive and significant effect on brand equity. Furthermore, brand equity also has a positive and significant effect on customer loyalty. The direct effect of the soft selling campaign on customer loyalty was found to be significant; however, the indirect effect through brand equity was stronger. This finding indicates that brand equity serves as an intervening variable that strengthens the relationship between the soft selling campaign and customer loyalty.